Uganda : Local Government Development Program - Mohan, P. C. (World Bank, Washington, DC, 2012)
The Uganda Local Government Development Program, with a credit equivalent to US$80.9 million, was implemented by the government over the period 2000-2004. The project was designed to scale up an earlier UN Capital Development Fund pilot to 30 districts (out of 56) so that policies and principles could be tested (and costed) on a larger scale and lessons learned used to develop national policy formulation within a sound fiscal framework. It had 4 objectives : (1) Test the feasibility of implementing constitutional and legal mandates with respect to decentralized service provision and devolution of the development budget through the provision of investment funds to the Local Governments; (2) Build the capacity of the Ministry of Local Government, the Local Government Finance Commission Secretariat, and a sub-set of the local governments for improved service delivery, accountability and transparency; (3) Test and institute alternative service delivery mechanisms through the private sector, beneficiary communities and other stakeholders in the Kampala City Council; (4) Monitor and evaluate project implementation for actual experience and good practices for formulating an appropriate strategy, implementation modalities, and phasing for eventual scaling-up, nationally, over time.